Copidothrips octarticulatus recorded from Tahiti, with first description of the male and larvae (Thysanoptera, Thripidae, Panchaetothripinae) - Goldarazena, Arturo; Michel, Bruno; Jacq, Fred (Zootaxa, 2021)
Heliothrips (Parthenothrips) octarcticulatus was originally described by Schmutz (1913) from Sri Lanka. Subsequently, Hood (1954) described from Taiwan a new genus and species Copidothrips formosus, and then Stannard and Mitri (1962) described a further new genus and species, Mesostenothrips kraussi, from Kiribati and Gibert Islands. Bhatti (1967, 1990), recognized that only a single genus and species was involved amongst these names, established the resultant synonymies, and recorded the species octarcticulatus from various localities between the Seychelles and five different Pacific Island groups. It has also been recorded from Northern Australia, and Thailand (ThripsWiki 2021) as well as Christmas Island in the Indian Ocean (Mound 2019). Despite these records, there is little reliable information about host plants and biology apart from Piper myristicum on Pohnpei island (Micronesia), and also damage caused to the leaves of Aglaonema and Spathoglottis at Darwin in Australia (Mound & Tree 2020). In this note, we add a further interesting host record and describe the previously unknown male as well as the larvae of this species.